1998
DOI: 10.1016/s1059-1311(98)80002-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient views on primary care services for epilepsy and areas where additional professional knowledge would be welcome

Abstract: In the past decade there has been increasing interest in the part that general practice can play in the care of people with epilepsy. Primary care services for epilepsy vary from practice to practice. Some studies have suggested that people with epilepsy prefer secondary care services and are not keen for their epilepsy to be managed in general practice, but much of the data were collected in secondary care. This study collected data from various sources about present provision of services, patient satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 9 publications
1
24
0
3
Order By: Relevance
“…We enrolled only epilepsy patients who volunteered to complete the survey on the 'Epilia' website and who attended epilepsy clinics at tertiary centers. One previous study cautioned that any conclusions about the organization of epilepsy care should draw data from a community patient sample [53]. However, our results seem to be in line with those of previous studies of patients with similar socio-demographic characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…We enrolled only epilepsy patients who volunteered to complete the survey on the 'Epilia' website and who attended epilepsy clinics at tertiary centers. One previous study cautioned that any conclusions about the organization of epilepsy care should draw data from a community patient sample [53]. However, our results seem to be in line with those of previous studies of patients with similar socio-demographic characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…Os PCE estão satisfeitos com atendimento como demonstrado na Tabela 1. 1,3,4,14,15,18,19,24,32,41 Essa afirmação torna-se discutível quando confrontadas às avaliações negativas a certas perguntas específicas desenvolvidas nos mesmos estudos. Existe uma grande insatisfação dos PCE com as informações recebidas pelos médicos, na maioria dos estudos os pacientes desejavam explicações sobre a causa da doença, fatores desencadeantes, tratamento, licença para dirigir e trabalho.…”
Section: Discussionunclassified
“…Dez artigos quantificaram as crises epilépticas. 1,3,4,8,10,13,14,24,26,38 Por questões metodoló-gicas, não é possível comparar a freqüência das crises entre os estudos. Cabe ressaltar que na maioria dos estudos, o grupo mais representativo de PCE apresentava uma ou mais crises por ano.…”
Section: Métodosunclassified
See 1 more Smart Citation
“…While people with controlled epilepsy may be cared for in primary care, it has been found that primary care services vary from practice to practice, and care is often reactive rather than proactive. 24 The new GP contract includes additional income for standards reached in epilepsy, and this may help to improve care.…”
Section: Are These Deaths Preventable?mentioning
confidence: 99%